Sex ed for social justice: Using principles of hip‐hop–based education to rethink school‐based sex education. Issue 5 (21st November 2022) - Guanci, Sin R.
Abstract: Forming and sustaining healthy relationships of any kind requires empathy, thought, communication and effort, all of which are learned skills. Many of these skills can and should be learned in a variety of places, including and especially in schools. One of the most appropriate venues for teaching interpersonal relationship skills in school is through 'sex ed' classes. I argue that student‐centred, anti‐racist, culturally affirming and appropriate, inclusive, egalitarian and relationship‐based learning environments are necessary for sex education that benefits all students. The principles of hip‐hop‐based pedagogies, including Christopher Emdin's Reality Pedagogy, Bettina Love's Abolitionist Pedagogy and Rawls and Robinson's Youth Culture Pedagogy can serve as a useful theoretical framework around which to build sex education curriculum and policy. School‐based sex education (SBSE) based on these principles may prove extremely beneficial not only to all students and their individual sense of identity and sexual autonomy but also to the general welfare of the public in the long run.